2011
DOI: 10.1002/smi.1321
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of individual factors, work‐related factors, and work–home interaction on burnout in female and male physicians: a longitudinal study

Abstract: The purpose of this study was to examine physician burnout in association with individual factors, work characteristics and work–home interaction (job performance‐based self‐esteem, goal orientation, value congruency, workload, autonomy, work–home conflict and work–home facilitation). This two‐wave panel study includes a sample of Norwegian physicians collected in 2003 (N = 683) and 2005 (N = 523). Hierarchical multiple regression analysis was used to test the assumed effects in male and female physicians sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
125
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(144 citation statements)
references
References 63 publications
10
125
1
8
Order By: Relevance
“…As our results identified in the multivariable analysis, payment method is a significant predictor of distress perceived by physicians when other predictors and confounding variables are considered in the assessment of this association. Gender [31,32] , time devoted to academic [9,33] and administrative duties [9] , and total number of working hours [34] are significant factors and they should be incorporated in distress models. Physicians self-select a payment method [35] and when they are paid by non-FFS schemes they tend to distribute their time differently [36] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As our results identified in the multivariable analysis, payment method is a significant predictor of distress perceived by physicians when other predictors and confounding variables are considered in the assessment of this association. Gender [31,32] , time devoted to academic [9,33] and administrative duties [9] , and total number of working hours [34] are significant factors and they should be incorporated in distress models. Physicians self-select a payment method [35] and when they are paid by non-FFS schemes they tend to distribute their time differently [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Regular working hours/week were found to confound the coefficients of payment method and proportion of complex patients; time devoted to academic duties confounded the coefficients of payment method; and time dedicated to administrative tasks confounded the coefficients of age group and payment method. Along with gender [31,32] , regular working hours/week, time devoted to academic duties, and time dedicated to administrative tasks were added to obtain an adjusted model with ten predictors (AIC = 806.97). Afterwards, interactions between predictors of distress and payment methods were tested.…”
Section: Multivariable Analysismentioning
confidence: 99%
“…Burnout is one of the most often studied outcomes of work-life conflict or imbalance [3][4][5]. It is considered as a phenomenon that affects more and more employees and has one of the most important effects on psychosocial wellbeing [6][7][8].…”
Section: Burnoutmentioning
confidence: 99%
“…-H4 -people who experience the positive work-home/ home-work interaction most often, have significantly higher index of professional efficacy than others. In recent years, gender differences in experiencing workhome interaction and burnout have been frequently studied [3,10,[31][32][33][34]. Some authors reported that balancing work and family duties poses a greater challenge for women than for men [3,10,31,34].…”
Section: Burnoutmentioning
confidence: 99%
“…The proportion of female physicians has increased considerably during the last 30 years, especially among family physicians [7] . Conflicts between work and home play significant roles in burnout, and the predictors of burnout differ by gender, with the stressors of exhaustion and disengagement stronger among women [8] . A study of physicians in Western Canada examined interactions among work-to-family conflicts by gender and parental status, finding a considerable percentage of physicians who are mothers reporting high levels of work-to-family conflicts [9] .…”
Section: Introductionmentioning
confidence: 99%